Quantification of eDNA to Map the Distribution of Cold-Water Coral Reefs - Kutti, Tina; Johnsen, Ingrid Askeland; Skaar, Katrine Sandnes; Ray, Jessica Louise; Husa, Vivian; Dahlgren, Thomas G. (Frontiers in Marine Science, 2020)
An effective management of vulnerable marine ecosystems is dependent on thorough knowledge of their location. Multibeam bathymetric mapping and targeted remotely operated vehicle (ROV) surveys are currently used to map areas impacted by industrial activities when vulnerable species are expected. However, multibeam bathymetric mapping is not always a possibility and surveying large areas using ROVs is expensive. Here, we developed a species-specific eDNA assay targeting a 178 bp fragment in the control region of the mitochondrial DNA of the cold-water coral (CWC) Lophelia pertusa. The aim was to test if concentrations of L. pertusa eDNA in seawater, determined using droplet digital PCR (ddPCR) technology, could be used to assess the broad scale distribution of CWCs in a region, to supplement multibeam mapping and direct targeted ROV surveys. Our assay successfully amplified L. pertusa DNA from seawater. In laboratory we documented an exponential decay rate of the targeted DNA fragment and a linear correlation between coral biomass and eDNA concentrations in flow through microcosms. The ability of the method to detect CWC reefs in situ was tested in the fjords south of Bergen, Norway, where such reefs are common. We tested five sites with, and five sites without, known reefs. Lophelia pertusa eDNA was detected in all 10 sites. However, concentrations were elevated by 5 to 10 times in water sampled off the two large reefs growing on vertical surfaces. Water sampled 10 m above CWC reefs growing on the flat seabed did not produce an equally clear eDNA signal, nor did single CWC colonies growing on vertical surfaces. Treating the eDNA as a passive particle with no active vertical or horizontal movement, we successfully modeled the dispersal of eDNA from the known CWC reefs in the region and achieved a good fit with measured eDNA concentrations. In all, our study demonstrated a great potential for eDNA measurements as a cost-efficient tool for a rapid screening of the broad scale distribution of CWC reefs growing on vertical surfaces (so called wall reefs) that cannot be imaged using traditional ship mounted downward looking multibeam echo-sounders and difficult to detect using ROVs alone.